Where are the provincial-level new records in China from the past 20 years, and which traits determine their shift directions? - Xing, Xiaoying; Wang, Xiaochen; Li, Xiang; Lan, Fangyuan; Deng, Zhangwen; Li, Yanqun; Li, Qingyuan (Frontiers in Ecology and Evolution, 2024)
Birds are sensitive to environmental changes and can drive range shifts rapidly due to their high mobility. Though previous studies have examined the associations between species traits and range shifts, whether species traits could still explain heterogeneity in shift directions remains poorly explored. Here, we compiled new bird records of China from 2000 to 2019 and analyzed species traits associated with apparent shift directions. We collected 350 provincial-level new records of birds belonging to 67 families of 22 orders. Of these, 32 are threatened, with 3 critically endangered, 11 endangered, and 18 vulnerable. Provinces in western China (i.e., Yunnan and Xizang) had relatively higher species richness of new recorded birds; this pattern was also reflected in the phylogenetic diversity we observed. In addition, provinces in northern China (i.e., Tianjin, Shandong, and Beijing) had relatively higher richness-controlled phylogenetic diversity. Phylogenetic overdispersion of new recorded bird communities was observed in 61.29% of provinces (19 of 31). The main shift directions indicated by new bird records were northward (with nearly 50% of birds moving NW, N and NE). Migration, hand-wing index (HWI), body mass, and range size are the four key factors that most significantly influence the shift directions in bird species, suggesting that bird movement toward newly suitable areas varies with species-specific traits. Together, these results demonstrate the importance of considering species ecological traits when predicting shift directions of birds.